The Roles of Customer Perception of Innovativeness and Engagement on Loyalty through Value Co-creation Behaviors: The Case of Food-delivery Service - Adinda Toti Paringan; Santi Novani (Binus Business Review, 2022)
The food delivery service that has gained popularity over the last few years should preserve its competitiveness by developing customer satisfaction and loyalty through customer value co-creation behaviors. However, there is still limited literature on understanding the antecedents and implications of customer value co-creation behavior in the service industry. The research aimed toÂ evaluate the effect of customer perceptions of innovativeness and customer engagement on value co-creation behavior. Also, this study wants to reveal the relationship between value co-creation behavior on customer satisfaction and loyalty in food delivery services, using Service-Dominant (S-D) logic perspective. A survey of Indonesian GoFood customers was conducted through an online questionnaire. Then, 349 complete responses were empirically analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The findings reveal that customer engagement and perceived innovativeness affect customer value co-creation behavior. However, customer participation does not immediately increase customer loyalty. Instead, it must be accompanied by an increase in customer satisfaction. By investigating the antecedents and implications of value co-creation behavior among food delivery service users, the research provides practitioners with viable business strategies for maximizing customer loyalty by evaluating service innovation and the customers' behavior in co-creation value. Moreover, the research contributes to the theoretical development of customer value co-creation behaviorsÂ and the foodservice business.